Comparison Of Branch Raise And Combined Shrinkage And Caving Methods - Charles Mitke (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
EXCLUDING top-slicing, and sublevel caving, large production caving methods may be divided into two general classes, the branch raise, or undercut caving method, and the combined shrinkage and caving method, each of which has a number of variations, the result of continual efforts towards obtaining lower costs and better extraction, by the introduction and substitution of minor improvements and modifications. EARLY CAVING METHODS Present caving methods are the cumulative result of developments covering a period of many years, with the most rapid growth during the past 15 years. They originated, presumably, from early English stoping methods, and, as far as is generally known, were first introduced in the Michigan iron district. They have had their greatest expansion and application in the large low-grade porphyry coppers. In their present form, they are probably a development and combination of sublevel caving and shrinkage (back-stoping on ore) with gravity handling of broken material. Sublevel caving, as practiced in the Michigan district today, is a combination of drift, or crosscut, mining, with top-slicing, and caving, supplemented by later refinements in the shape of mechanized handling of broken ore. A height of anywhere from 16 to 20 ft. is generally taken, and the ore is drilled and blasted along the drift or crosscut for half this height (say 8 to 10 ft.), after which the upper 8 to 10 ft. caves and breaks of its own weight, with comparatively little assistance from drilling. This